Nanostructural Materials for Energy Storage Systems. (9th January 2011) - Buczek, Bronislaw
Abstract : The aim of this study was to assess of carbonaceous monoliths used for adsorption cooling systems. The carbonaceous monoliths prepared from coal precursors are obtained. The porous structure of monoliths was evaluated on the basis of nitrogen adsorption-desorption data. The investigated monoliths have significantly developed microporous structure. The large specific area of carbonaceous monoliths (about 2000 m 2 /g) and volume of micropores are observed. Methanol adsorption isotherms and heat of wetting using methanol was determined. Results show that monoliths materials are high adsorption capacity of methanol and heat of wetting, which can improve of heat exchange and efficiency in processes of refrigeration and air conditioning.